Q. 285.0( 1 Vote )

Fill in the blanks to make the statements true.


Answer :

According to the law of indices:

(am)n = a(m × n)


Applying the same law here,


In the above question,


a = 6/13


m = 5


n = 2


m × n = 5 × 2


= 10


[(6/13)5]2 = (6/13)10


Again we have another law of indices which is as follows:


am ÷ an = a (m-n)


Here in the question,


a = 6/13


m = 10


n = 10


m – n = 10 - 10


= 0


(6/13)10 ÷ (6/13)10 = (6/13)0


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.